PENGARUH PARTISIPASI ANGGOTA DAN KEMAMPUAN PENGURUS TERHADAP SHU ANGGOTA KOPERASI - Kikky, Benedhikta (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis study aims to examine and discuss the phenomenon of member participation and the ability of  the management  to the remaining business results of Credit Union Khatulistiwa Bakti. This research use quantitative method, and sample of this research is counted 95 member cooperative. Data collection techniques used are: Indirect Communication Techniques, direct Communication Techniques. While the data collection tool is: questionnaire research, interview guide. The results of this study indicate that: there is partial influence of member participation to the rest of business result of Credit union member Khatulistiwa Bakti with value of sig 0,001 <0,050. There is partially influence the ability of management to the rest of business result of credit union member Khatulistiwa Bakti office of Simpang Tiga  with sig value 0,003 <0,050.  There is a linear influence between the participation of members on the ability of the board with the value of siginifikansi deviation from linierity 0,0533> 0,050. There is significant and positive influence simultaneously member participation and ability of management to the rest of business result of member of credit union Khatulistiwa Bakti resume table Statistical product and service solution obtained significance value 0,003 <0,050, and big influence of coefficient of determination R²) of 12,2%.Keywords: participation, management ,Remaining bussines result